2016
DOI: 10.2337/dc15-2721
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Regional Brain Responses to Food Ingestion After Roux-en-Y Gastric Bypass and the Role of Gut Peptides: A Neuroimaging Study

Abstract: OBJECTIVEImproved appetite control, possibly mediated by exaggerated gut peptide responses to eating, may contribute to weight loss after Roux-en-Y gastric bypass (RYGB). This study compared brain responses to food ingestion between post-RYGB (RYGB), normal weight (NW), and obese (Ob) unoperated subjects and explored the role of gut peptide responses in RYGB. RESEARCH DESIGN AND METHODS Neuroimaging with [18 F]-fluorodeoxyglucose (FDG) positron emission tomography was performed in 12 NW, 21 Ob, and 9 RYGB (18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The resulting void in cell mass would then conceivably lead to an increase in T2W SI and a decrease in FA values due to increases in hypothalamic water content and freer water movement, respectively. The enhanced hypothalamic function (58) and resting connectivity (59) previously reported for patients after RYGB supports the second interpretation. Moreover, CSF levels of the antiinflammatory cytokine IL-10 has been found to increase in patients after RYGB (59).…”
Section: Figure 4 Relationships Between Bmi Body Fat Mass Circulatsupporting
confidence: 74%
“…The resulting void in cell mass would then conceivably lead to an increase in T2W SI and a decrease in FA values due to increases in hypothalamic water content and freer water movement, respectively. The enhanced hypothalamic function (58) and resting connectivity (59) previously reported for patients after RYGB supports the second interpretation. Moreover, CSF levels of the antiinflammatory cytokine IL-10 has been found to increase in patients after RYGB (59).…”
Section: Figure 4 Relationships Between Bmi Body Fat Mass Circulatsupporting
confidence: 74%
“…The altered functional connectivity of long-range subcortical areas involved in viscerosensitivity and nociception may occur (Figure 1). In particular, RYGB has been repeatedly associated with altered functional connectivity in response to food image or food ingestion (Frank et al, 2014;Hunt et al, 2016;Olivo et al, 2017;Baboumian et al, 2019). In the case of food image, brain activity was comparable in normal-weight and RYGB subjects, thus making it difficult to distinguish the contribution of body weight from that of the bypass surgery (Frank et al, 2014).…”
Section: Brain Dysconnectivity and Neural Entanglementmentioning
confidence: 99%
“…Substantiating the results from animal models, there are compelling clinical findings which suggest that RYGB targets the hypothalamic melanocortinergic system to influence feeding responses and body weight. Specifically, in a recent 18 F-fluorodeoxyglucose PET imaging study, hypothalamic metabolic activity 90 minutes following a fixed meal was found to reach supraphysiological levels (approximately double that of normal-weight controls) in patients postoperatively [35]. Because this was largely independent of gut hormone release [35], potential mediating peripheral factors could derive from gut microbiota, namely Escherichia coli, whose abundance has been shown to markedly increase in humans and animals after RYGB [16][17][18] (Figure 2A).…”
Section: The Brain Melanocortinergic Systemmentioning
confidence: 93%
“…Specifically, in a recent 18 F-fluorodeoxyglucose PET imaging study, hypothalamic metabolic activity 90 minutes following a fixed meal was found to reach supraphysiological levels (approximately double that of normal-weight controls) in patients postoperatively [35]. Because this was largely independent of gut hormone release [35], potential mediating peripheral factors could derive from gut microbiota, namely Escherichia coli, whose abundance has been shown to markedly increase in humans and animals after RYGB [16][17][18] (Figure 2A). Work performed on rats first suggested that these bacteria Glossary Dopaminergic system: in the brain, this comprises neurons which express tyrosine hydroxylase and that synthesize dopamine as well as their downstream target neurons that express dopamine receptors (D1R-D5R).…”
Section: The Brain Melanocortinergic Systemmentioning
confidence: 93%